Ustrushona’s Road Structures on the Great Silk Road - og`lu, Saidov Javohir Olimjon (European Journal of Life Safety and Stability (2660-9630), 2022)
This article contains the author’s thoughts and comments on the fact that the Jizzakh oasis has been one of the cradles of ancient civilization and culture, its convenient geographical location and nature, rabod, caravanserais and cisterns located in the oasis.